Exploring Methacrylated Gellan Gum 3D Bioprinted Patches Loaded with Tannic Acid or L-Ascorbic Acid as Potential Platform for Wound Dressing Application - Federica Scalia; Alessandra Maria Vitale; Domiziana Picone; Noemi De Cesare; Maria Swiontek Brzezinska; Beata Kaczmarek-Szczepanska; Alfredo Ronca; Barbara Zavan; Fabio Bucchieri; Marta Anna Szychlinska; Ugo D’Amora (Gels)
To improve wound healing, advanced biofabrication techniques are proposed here to develop customized wound patches to release bioactive agents targeting cell function in a controlled manner. Three-dimensional (3D) bioprinted “smart” patches, based on methacrylated gellan gum (GGMA), loaded with tannic acid (TA) or L-ascorbic acid (AA) have been manufactured. To improve stability and degradation time, gellan gum (GG) was chemically modified by grafting methacrylic moieties on the polysaccharide backbone. GGMA patches were characterized through physicochemical, morphological and mechanical evaluation. Kinetics release and antioxidant potential of TA and AA as well as antimicrobial activity against common pathogens Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli in accordance with ISO 22196:2011 are reported. The cytocompatibility of the patches was demonstrated by direct and indirect tests on human dermal fibroblasts (HDF) as per ISO 10993. The positive effect of GGMA patches on cell migration was assessed through a wound healing assay. The results highlighted that the patches are cytocompatible, speed up wound healing and can swell upon contact with the hydration medium and release TA and AA in a controlled way. Overall, the TA- and AA-loaded GGMA patches demonstrated suitable mechanical features; no cytotoxicity; and antioxidant, antimicrobial and wound healing properties, showing satisfactory potential for wound dressing applications.